Fair game: exploring the dynamics, perception and environmental impact of ‘surplus’ wild foods in England 10kya-present - Sykes, Naomi (Taylor and Francis, 2017)
This paper brings together zooarchaeological data from Neolithic to Post-medieval sites in England to explore the plasticity of cultural attitudes to the consumption of wild animals. It shows how, through time, game has been considered variously as ‘tabooed’ and ‘edible’, each having implications for patterns of biodiversity and wildlife management. The essential points being made are that deeper-time studies can reveal how human perceptions of ‘surplus foods’ have the potential to both create and remedy problems of environmental sustainability and food security. Perhaps more significantly, this paper argues that understanding the bio-cultural past of edible wild animal species has the potential to transform human attitudes to game in the present. This is important at a time when food security and the production of surplus are pressing national and global concerns.